Seawater-resistant and damage-resistant skin-like elastomer as well as preparation method and application thereof

By introducing cation-π interactions into polyurethane, the dense nanophase of hydrogen bond clusters is solved, and the performance of existing skin-like elastomers in seawater environments is achieved, and good mechanical properties, damage resistance and seawater resistance are achieved. The combination of the company has a wide range of marine application potential.

CN119390925AActive Publication Date: 2025-02-07DONGHUA UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411210656.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-02-07
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Existing skin-like elastomers are prone to expansion and physical bond damage in seawater environments, resulting in reduced performance and difficult to effectively apply in marine environments.

Method used

By introducing cation-π interaction into polyurethane, dense nanophase of hydrogen bond clusters is induced to form, thereby improving the mechanical properties and damage resistance of the elastomer, and protecting the hydrogen bond clusters in a high-salt environment to maintain the elastomer's seawater resistance performance.

Benefits of technology

It realizes the combination of mechanical properties, damage resistance and seawater resistance of cephalopod-like skin, and can maintain efficient performance in harsh marine environments and has a wide range of application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390925A_ABST
    Figure CN119390925A_ABST
Patent Text Reader

Abstract

The invention relates to a seawater-resistant and damage-resistant skin-like elastomer and a preparation method and application thereof, and the seawater-resistant and damage-resistant skin-like elastomer is obtained by introducing cation-pi interaction into a polyurethane preparation process to induce formation of a compact nanophase of a hydrogen bond cluster. The method has good mechanical properties, damage resistance and seawater resistance of cephalopod-like animal skin, can have very high potential in underwater application in the aspects of exploration and utilization of marine resources, and particularly has good application prospects in coping with challenges brought by severe marine environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer elastomers, and particularly relates to a seawater-resistant and damage-resistant skin-like elastomer and a preparation method and application thereof. Background Art

[0002] In the process of hundreds of millions of years of evolution, organisms in nature have become highly rational, scientific and advanced in many aspects. Among the numerous aquatic and terrestrial species, cephalopods have complex deformation, dynamic optical camouflage and environmental perception capabilities due to their unique protein system. Researchers have long used squid skin as a biological inspiration for the development of smart materials, such as soft robots [Angew.Chem.Int.Ed.2011,50,1890; Nature 2015,521,467; Sci.Robot.2023,8,eadh7852; Chin.J.Polym.Sci.2022,40,384; Adv.FiberMater.2022,4,1209; Adv.FiberMater.2022,4,98] and adhesives [Nature 2017,546,396; Smart Mater.Med.2023,4,294]. Squid skin exhibits strain hardening mechanical behavior, where the initially soft and compliant skin quickly hardens under severe deformation, resulting in an increase in elastic modulus by several orders of magnitude to prevent damage. In addition, squid skin is very strong and can resist tearing, punctures, and seawater, which can protect squids from predators and survive in harsh environments.

[0003] Inspired by the structure of cephalopod skin, different networks with different stiffness are integrated together to simulate strain hardening properties through a progressive response to strain. [Nat. Commun. 2020, 11, 1107; Nat. Commun. 2021, 12, 4082; Adv. Mater. 2020, 32, 2003761] Sheiko et al. developed bottle brush elastomers containing flexible strands and rigid backbones to replicate skin-like mechanical behaviors. [Science 2018, 359, 1509] Skin-like elastomers with hybrid cross-linked networks were developed by combining covalent bonds and hydrogen bonds into one network. [Adv. Fiber Mater. 2022, 4, 98] Wu et al. developed self-healing skin-like ionic elastomers by introducing entropy-driven supramolecular zwitterionic reconfigurable networks in hydrogen-bonded networks.

[0004] However, most reported skin-like elastomers usually encounter some problems that seriously hinder their further application. These elastomers usually adopt low cross-linking density and weak cross-linking to ensure their inherent softness, resulting in poor strength and tear resistance. In addition, most physical cross-linking is easily affected by certain environmental factors (such as water or ions). Due to the influence of salt ions on the strength of elastomers, the inevitable expansion of elastomers and the destruction of physical bonds seriously hinder the application of elastomers in sweat or marine environments. Therefore, a new molecular design is needed to combine the above properties in a synthetic elastomer. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a seawater-resistant and damage-resistant skin-like elastomer and its preparation method and application. The elastomer has good mechanical properties, damage resistance and seawater resistance of cephalopod-like skin.

[0006] The invention provides a seawater-resistant and damage-resistant skin-like elastomer, which is obtained by introducing cation-π interaction into the polyurethane preparation process to induce the formation of a dense nanophase of hydrogen bond clusters.

[0007] Preferably, the cation-π interaction is provided by aromatic groups including one or more of indole, benzene, pentafluorobenzene, pyrrole, and naphthalene and cationic groups including one or more of lithium sulfonate, sodium sulfonate, potassium sulfonate, and quaternary ammonium salt.

[0008] Preferably, the polyurethane is obtained by reacting polyether polyol or polyester polyol with polyisocyanate.

[0009] Preferably, the polyisocyanate includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, dicyclohexylmethane diisocyanate, xylylene diisocyanate, triphenylmethane triisocyanate, L-lysine triisocyanate, and polymethylene polyphenyl polyisocyanate.

[0010] Preferably, the polyether polyol includes one or more of polytetramethylene ether glycol, polypropylene glycol, polyethylene glycol, and polyglycerol; the weight average molecular weight of the polyether polyol is 500-10000; the polyester polyol includes one or more of polyhexamethylene adipate diol, polybutylene adipate diol, polypropylene adipate diol, polyethylene adipate diol, polybutylene phthalate diol, polycaprolactone diol, and polycaprolactone triol, and the weight average molecular weight of the polyester polyol is 500-10000.

[0011] Preferably, the general structural formula of the skin-like elastomer is:

[0012]

[0013] The value range of x, y, and z is 1-40.

[0014] The present invention also provides a method for preparing a seawater-resistant and damage-resistant skin-like elastomer, comprising the following steps:

[0015] (1) indole-3-carboxaldehyde and 2-amino-1,3-propanediol are mixed in a molar ratio of 1:(1-1.5), refluxed for 24 hours under the action of a catalyst, and then post-treated to obtain an aromatic monomer IAPD;

[0016] (2) Weigh polyether polyol or polyester polyol and sodium salt of N,N-di(2-hydroxyethyl)-2-aminoethanesulfonic acid in a molar ratio of 1:(0.13-0.33), add polyisocyanate in a molar ratio of 1:(1.25-1.67) to the polyether polyol or polyester polyol into a reaction flask under a nitrogen environment and stir to react for 4-6 hours; add aromatic monomer IAPD in a molar ratio of 1:(0.13-0.33) to the polyether polyol or polyester polyol into a reaction flask under a nitrogen environment and react at 80-90°C for 12-18 hours, and vacuum dry to constant weight to obtain a seawater-resistant and damage-resistant skin-like elastomer.

[0017] Preferably, the mixed solvent in step (1) is one or more of ethanol, methanol and N,N'-dimethylformamide.

[0018] Preferably, the catalyst in step (1) is one or more of acetic acid and sodium carbonate.

[0019] The reaction equation of the present invention is as follows

[0020]

[0021] The present invention also provides a skin-like elastomer that is resistant to seawater and damage and is used in the fields of marine resource exploration and utilization, medical equipment, etc.

[0022] The principle of the present invention is:

[0023] Cation-π interactions are introduced into polyurethane to induce the formation of a dense nanophase of hydrogen-bonded clusters, thereby giving the elastomer skin-like mechanical behavior and damage resistance. At the same time, high-concentration salt solutions reduce the electrostatic repulsion between ions, reduce the distance between molecular chains, and increase cation-π interactions, thereby protecting the hydrogen-bonded cluster nanophase from seawater corrosion, making the elastomer resistant to seawater and useful for underwater applications in the exploration and utilization of marine resources.

[0024] Beneficial Effects

[0025] The present invention has good mechanical properties, damage resistance and seawater resistance of cephalopod-like skin, and has high potential for underwater application in the exploration and utilization of marine resources, especially in dealing with the challenges brought by the harsh marine environment, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (a) is a schematic diagram of the structure of cephalopod skin and (b) is a schematic diagram of the structure of the elastomer of the present invention.

[0027] Figure 2 It is the infrared spectrum of the elastomer of the present invention.

[0028] Figure 3 It is the mechanical property of the elastomer of the present invention.

[0029] Figure 4 It is the tear resistance of the elastomer of the present invention.

[0030] Figure 5 ab is the puncture resistance of the elastomer of the present invention.

[0031] Figure 6 ab is the long-term seawater resistance of the elastomer of the present invention.

[0032] Figure 7 is the hydrogen spectrum of monomer IAPD. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] Example 1

[0035] The preparation of the seawater-resistant and damage-resistant skin-like elastomer of the present invention comprises the following steps:

[0036] Step 1: Preparation of aromatic monomer IAPD

[0037] Indole-3-carboxaldehyde and 2-amino-1,3-propanediol were mixed in a molar ratio of 1:1, dissolved in 100 mL of ethanol, and refluxed for 24 hours under the action of 6 drops of acetic acid catalyst. The magnesium sulfate was filtered out, and part of the solvent was removed by rotary evaporation. Ethyl acetate was added for recrystallization to obtain a light yellow solid IAPD monomer, which was vacuum dried to constant weight.

[0038] The reaction equation of the IAPD is as follows:

[0039]

[0040] The hydrogen spectrum of the IAPD is as follows Figure 7 As shown, the data are: 11.45 ppm is the chemical shift of the amino group in indole, 7.07-8.44 ppm is the chemical shift of the benzene ring and -N=CH- double bond in the indole imine group, and 3.16-4.48 ppm is the chemical shift of CH and CH2 in the propylene glycol group.

[0041] Step 2: Preparation of skin-like elastomer ISPU

[0042] According to the molar ratio of 1:0.13, 2000 molecular weight polytetrahydrofuran (PTMG) and sodium salt of N,N-di(2-hydroxyethyl)-2-aminoethanesulfonic acid (BES-Na) were weighed and placed in a 250mL Shrek bottle, and the water was removed by vacuum at 90℃. After cooling to 85℃, 5mL N,N-dimethylformamide (DMF) was used to dissolve hexamethylene diisocyanate (HDI) with a molar ratio of 1:1.25 to PTMG in a nitrogen environment, and added to the reaction bottle and stirred for 4 hours. The aromatic monomer IAPD with a molar ratio of 1:0.13 to PTMG was dissolved in 5mL DMF, added to the reaction bottle in a nitrogen environment and reacted at 85℃ for 12 hours. After the reaction was completed, the reaction solution was introduced into ether for precipitation, and vacuum dried to constant weight to obtain a light yellow solid ISPU elastomer. ISPU elastomer was dissolved in tetrahydrofuran, and the obtained solution was poured into a polytetrafluoroethylene mold, placed in a 40°C oven for 48 hours to remove the solvent, and then vacuumed and placed at 80°C for 24 hours to remove the remaining solvent to obtain an ISPU elastomer film.

[0043] Example 2

[0044] This embodiment is basically the same as the embodiment 1, except that in the first step of preparing the aromatic monomer IAPD, the ratio of indole-3-carboxaldehyde to 2-amino-1,3-propanediol is 1:1.2.

[0045] Example 3

[0046] This embodiment is basically the same as the embodiment 1, except that in the first step of preparing the aromatic monomer IAPD, the ratio of indole-3-carboxaldehyde to 2-amino-1,3-propanediol is 1:1.5.

[0047] Example 4

[0048] This embodiment is basically the same as Embodiment 1, except that in the second step of preparing the skin-like elastomer ISPU film, the ratio of PTMG, BES-Na, IAPD and HDI is 1:0.21:0.21:1.43.

[0049] Example 5

[0050] This embodiment is basically the same as Embodiment 1, except that in the second step of preparing the skin-like elastomer ISPU film, the ratio of PTMG, BES-Na, IAPD and HDI is 1:0.33:0.33:1.67.

[0051] The performance test method is as follows:

[0052] The polymer film was cut into dumbbell-shaped specimens of 20mm×4mm×0.4mm, and stretched to fracture at a rate of 50mm / min using a universal tensile machine, and the tensile mechanical curve was measured. The fracture energy test used a single-sided notched specimen (slit length was 1mm), and the polymer film was cut into dumbbell shapes with and without notches of 20mm×4mm×0.4mm, and the tensile test was performed at a tensile rate of 50mm / min. Fracture energy (G c ) is calculated by the following formula: The polymer samples with an average thickness of 0.8 mm were subjected to puncture resistance test according to the standard GB / T 37841-2019. The polymer film was cut into dumbbell-shaped specimens of 20 mm × 4 mm × 0.4 mm, immersed in 0.7 M sodium chloride aqueous solution, stretched to fracture at a rate of 50 mm / min using a universal tensile machine, and the tensile mechanical curve after immersion was measured.

[0053] The performance test results are as follows:

[0054] (1) Figure 2 is the infrared spectrum of the elastomer ISPU prepared in Example 5, 1210 cm -1 and 1040cm -1 The characteristic peak of sulfonic acid group (-S(=O)2) is 997cm -1 and 746cm -1 The peaks at the bottom are the characteristic peaks of the carbon-nitrogen bond (-CN-) of the indole ring and the aromatic ring.

[0055] (2) Figure 3 It is the tensile mechanical curve of the elastomer ISPU prepared in Examples 3-5. The engineering stress of Example 3 is 8.5 MPa, and the elongation at break is 1598%. The engineering stress of Example 4 is 26.1 MPa, and the elongation at break is 1197%. The engineering stress of Example 5 is 35.3 MPa, and the elongation at break is 1122%.

[0056] (3) Figure 4 is the notched tensile mechanical curve of the elastomer ISPU prepared in Example 5, and the calculated tear energy is 103.7 kJm -2 .

[0057] (4) Figure 5This is a physical picture of the puncture test of the elastomer ISPU prepared in Example 5 ( Figure 5 a) and puncture mechanical curve ( Figure 5 b), the puncture force is 34.4N.

[0058] (5) Figure 6 The tensile mechanical curves of the elastomer ISPU prepared in Example 5 before and after being immersed in 0.7M sodium chloride aqueous solution for 14 days ( Figure 6 a) and physical picture ( Figure 6 b), after 14 days, the stress retention of the elastomer is 99%.

Claims

1. A skin-like elastomer that is resistant to seawater and damage, characterized in that: The polyurethane is prepared by introducing cation-π interactions into the polyurethane preparation process to induce the formation of a dense nanophase of hydrogen-bonded clusters.

2. The skin-like elastomer according to claim 1, characterized in that: The cation-π interaction is provided by the aromatic group and the cationic group.

3. The skin-like elastic body according to claim 1, characterized in that: The polyurethane is obtained by reacting polyether polyol or polyester polyol with polyisocyanate.

4. The skin-like elastic body according to claim 3, characterized in that: The polyisocyanate includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, dicyclohexylmethane diisocyanate, xylylene diisocyanate, triphenylmethane triisocyanate, L-lysine triisocyanate, and polymethylene polyphenyl polyisocyanate.

5. The skin-like elastic body according to claim 3, characterized in that: The polyether polyol includes one or more of polytetramethylene ether glycol, polypropylene glycol, polyethylene glycol, and polyglycerol; the weight average molecular weight of the polyether polyol is 500-10000; the polyester polyol includes one or more of polyhexane adipate diol, polybutylene adipate diol, polypropylene adipate diol, polyethylene adipate diol, polybutylene phthalate diol, polycaprolactone diol, and polycaprolactone triol; the weight average molecular weight of the polyester polyol is 500-10000.

6. The skin-like elastic body according to claim 1, characterized in that: The general structural formula of the skin-like elastomer is: Among them, the value range of x, y, and z is 1-40.

7. A method for preparing a seawater-resistant and damage-resistant skin-like elastomer according to any one of claims 1 to 6, comprising the following steps: (1) indole-3-carboxaldehyde and 2-amino-1,3-propanediol are mixed in a molar ratio of 1:(1-1.5), refluxed for 24 hours under the action of a catalyst, and then post-treated to obtain an aromatic monomer IAPD; (2) Weigh polyether polyol or polyester polyol and sodium salt of N,N-di(2-hydroxyethyl)-2-aminoethanesulfonic acid in a molar ratio of 1:(0.13-0.33), add polyisocyanate in a molar ratio of 1:(1.25-1.67) to the polyether polyol or polyester polyol into a reaction flask under a nitrogen environment and stir to react for 4-6 hours; add aromatic monomer IAPD in a molar ratio of 1:(0.13-0.33) to the polyether polyol or polyester polyol into a reaction flask under a nitrogen environment and react at 80-90°C for 12-18 hours, and vacuum dry to constant weight to obtain a seawater-resistant and damage-resistant skin-like elastomer.

8. The preparation method according to claim 7, characterized in that: The mixed solvent in step (1) is one or more of ethanol, methanol and N,N'-dimethylformamide.

9. The preparation method according to claim 7, characterized in that: The catalyst in step (1) is one or more of acetic acid and sodium carbonate.

10. Use of the seawater-resistant and damage-resistant skin-like elastomer according to any one of claims 1 to 6 in marine resource exploration and utilization and medical devices.

Citation Information

Patent Citations

  • Dyhydroxyl sulphonate hydrophilic monomer and preparation method thereof

    CN103232372A

  • Degradable main chain quaternary ammonium salt type polycation and preparation method thereof

    CN105482105A

  • Electrically Conductive Films Formed From Dispersions Comprising Conductive Polymers and Polyurethanes

    US20100270055A1

  • Rigid foams

    US20200339732A1

  • Bio-based coatings and adhesives using oils of physaria fendleri and euphorbia lagascae

    US20210292623A1